Highly efficient piezocatalytic composite with chitosan biopolymeric membranes and bismuth ferrite nanoparticles for dye decomposition and pathogenic S. aureus bacteria killing - Liu, Yunhong; Roy, Jhilik; Roy, Shubham; Hoque, Nur Amin; Guo, Bing (Frontiers in Chemistry, 2024)
Untreated wastewater harbors dangerous pathogens, chemicals, and pollutants, posing grave public health threats. Nowadays, there is a rising demand for eco-friendly technologies for wastewater treatment. Recently, piezoelectric materials-based wastewater treatment technology has captured considerable interest among researchers because of its noninvasiveness and rapidity. Herein, a highly efficient piezoelectric composite material is designed with chitosan-incorporated bismuth ferrite (BFO) nanocrystals, to decompose pollutants and ablate bacteria in wastewater. On one hand, piezoelectric BFO has shown exclusive piezo-coefficient for ultrasound-mediated reactive oxygen species (ROS) production. On the other hand, chitosan depicts its biocompatible nature, which not only promotes cellular adhesion but also significantly elevates the ROS production capabilities of BFO under ultrasound. The synergistic effect of these two piezoelectric units in one composite entity shows an improved ROS production, eradicating ∼87.8% of Rhodamine B within 80 min under soft ultrasound treatment (rate constant, k ≈ 0.02866 min−1). After performing the scavenger experiment, it has been found that hydroxyl radicals are the dominating factor in this case. Further, the reusability of the composite piezocatalyst is confirmed through multiple cycles (five times) of the same experiment. The high polarizability of the composite material facilitates the generation of piezoelectric power through finger tapping (∼12.05 V), producing substantial instantaneous piezo-voltage. Moreover, the sample exhibits remarkable antibacterial activity, with nearly 99% bacterial eradication within 30 min. This indicates a significant advancement in utilizing biopolymeric composites incorporated with BFO for fabricating versatile devices with multidimensional applications.